A descontinuidade do tempo: uma aproximação entre as noções de duração em Bergson e Descartes - Silva, Elaine Guinevere de Melo (2014)
A comparative study between Bergson and Descartes regarding their notion of duration, resulted in the development and composition of this research theme, which shows and ponders about the meaning and consequences of the conception of time from both thinkers within their own philosophies and methods of knowledge. The Bergsonian method of intuition and the mechanistic Cartesian model are presented and compared in terms of appropriateness to their respective metaphysical propositions. Relevant aspects of the activity of memory and intellect are highlighted to show the divergence between the views of Descartes and Bergson about these faculties. We discussed the Cartesian thesis of the independence between the time instants, in which duration is seen as a multitude of parts divisible and independent. This thesis was analyzed on the basis of the critique of the spatial representation of time, through which, the aspects of time spatialization were highlighted, such as simultaneity, immobility and discontinuity. The temporality of psychological states was also approached from Bergsonian and Cartesian philosophy. The continuous and uninterrupted movement of thought, described by Descartes, keeps resemblance to the description of the dynamics of consciousness duration in Bergson. However, only the second one paid attention to the indivisible character of duration as creation and incessant flow.